Academic Differences in BSN Admission Routes: Implications for Persistence. - Jennings, Leslie A.; Urban, Regina W.; Cipher, Daisha J. (Journal of Nursing Education, 2023)
Background: To increase retention of prelicensure nursing students, several routes are used for admission to nursing programs. Students can be accepted as an early matriculation (EM) student at the point of university admission or they can follow a traditional competitive approach (TR) for admission. Method: A retrospective matched cohort study design was used to explore the differences among selected academic variables in two groups of prelicensure undergraduate students (n = 136) in the same program. Results: EM students had significantly lower science grade point averages (GPAs), pre-program GPAs, and junior-level GPAs than TR students. However, there were no significant differences between the two groups in scores on the RN Fundamentals ATI examination, an important predictor of future NCLEX-RN success. Conclusion: EM students were as successful as their counterparts on standardized examinations in the first semester of a nursing program. More research is needed to understand program outcomes associated with students entering nursing programs via different routes. [J Nurs Educ. 2023;62(5):302–306.]